1994
DOI: 10.1046/j.1537-2995.1994.34794330014.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of hepatitis C virus RNA in immune globulins

Abstract: Many immune globulin preparations contained HCV RNA, with levels depending upon both the type of starting plasma and the manufacturing process. Exposure to ethanol did not appear to affect the physical characteristics of HCV RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
(1 reference statement)
1
21
1
Order By: Relevance
“…Furthermore, the HCV in this lot had a low buoyant density, 1.08 g͞ml (15) (determined by sucrose gradient ultracentrifugation), suggesting that the virus was not complexed with antibody (3,21). This finding was in contrast to the buoyant density of HCV recovered from anti-HCV-positive immune globulin, 1.16 g͞ml, as found in intramuscular globulin derived from plasma that was not screened for anti-HCV (13) or found in plasma from patients chronically infected with HCV (21).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Furthermore, the HCV in this lot had a low buoyant density, 1.08 g͞ml (15) (determined by sucrose gradient ultracentrifugation), suggesting that the virus was not complexed with antibody (3,21). This finding was in contrast to the buoyant density of HCV recovered from anti-HCV-positive immune globulin, 1.16 g͞ml, as found in intramuscular globulin derived from plasma that was not screened for anti-HCV (13) or found in plasma from patients chronically infected with HCV (21).…”
Section: Discussionmentioning
confidence: 80%
“…Before 1993, globulin-related transmission of hepatitis C by licensed products had not been reported in the U.S. The mechanism of this apparent safety of immune globulins before the Gammagard incident was unknown, although the possible neutralization of HCV by antibodies in products not screened for such antibodies had long been suspected (13,32). Epidemiological and laboratory follow-up studies of the Gammagard incident revealed the following:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations